Current Development in Bioanalytical Sample Preparation Techniques - SAKSHI SANGALE SAKSHI; PRAVIN R. DIGHE; MANOJ R KUMBHARE (Baghdad Journal of Biochemistry and Applied Biological Sciences)
The preparation of the sample is the most important stage in bioanalysis. Proteins, salts, and other organic compounds with chemical characteristics similar to the target analytes are commonly found in biological samples. As a result, sample preparation is an essential step that improves matrix suitability for analysis in multiple ways, including by separating the analytes and clearing the matrix of obstructive elements. Innovative sample preparation techniques have been more and more popular over the last 10 years due to their advantages over conventional techniques in terms of accuracy, automation, simplicity of sample preparation, storage, and delivery. This article’s goal is to raise awareness of the most recent advancements in the processing of bioanalytical samples. Different extraction stages are provided by modern techniques, such as sorbent-based microextraction, and the advantages of bioanalytical approaches have been highlighted.